Penerapan Positioning Therapy terhadap Peningkatan Perfusi Serebral pada Pasien Stroke Iskemik - Sindi Lailatul Muasanah; Erida Fadila; Dwiyanti Purbasari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Ischemic stroke is one of the neurological conditions that can cause cerebral perfusion disorders due to reduced blood flow to the brain. One of the evidence-based nursing interventions used to optimize cerebral perfusion is positioning therapy, specifically the 30° head up position. This study aims to determine the effectiveness of positioning therapy on increasing cerebral perfusion in ischemic stroke patients. The research method is in the form of literature review of 12 articles published in the 2020–2025 period, with data sources from Google Scholar, PubMed, ScienceDirect, and Garuda. The results of the study show that most studies support the effectiveness of the 30° head up position in improving cerebral perfusion. This is characterized by an increase in Cerebral Perfusion Pressure (CPP), an increase in the Glasgow Coma Scale (GCS), an increase in oxygen saturation (SpO₂), and a decrease in Intracranial Pressure (ICP). These findings confirm that positioning therapy is a simple, safe, and evidence-based nursing intervention to improve cerebral perfusion in ischemic stroke patients. The implication of this study is the need to apply positioning therapy as part of the standard nursing practice in the management of ischemic stroke patients to support the improvement of clinical conditions and quality of life.